USE OF COVERED SELF-EXPANDABLE NITINOL STENT FOR ANASTOMOTIC BILIARY STRUCTURE MANAGEMENT AFTER LIVER TRANSPLANTATION: THE FIRST EXPERIENCE - M. N. Kornilov; V. V. Gvozdik; A. N. Lotov; Y. G. Moysyuk (Вестник трансплантологии и искусственных органов)
Aim. The aim of this study focuses on the first experience with self-expandable stents, analysis of its efficacy and safety in the treatment of anastomotic strictures after liver transplantation. Materials and methods. There’re 136 liver transplantations performed from 2004 till 2012. To correct anastomotic strictures we’ve used only the self-expandable coated nitinol stent. We performed stenting in 7 recipient. Result. In 131 liver transplant recipients incidence of biliary strictures has been 5.3%. All of 5 patients have been managed by retrograde or antegrade way. Conclusion. Our first experience demonstrate efficacy and safety of the used tecniques up to 24 months. The analysis of more long-term results is required.